Renal pelvis metastasis following surgery for breast angiosarcoma: a case report and literature review - Guo, Fuyu; Sun, Shiwei; Niu, Xiangnan; Wang, Yue; Yao, Wei; Yue, Peng; Deng, Xiaoqian; Shang, Jiwen; Zhang, Yangang (Frontiers in Oncology, 2024)
Renal metastasis of breast angiosarcoma is rare. This article reports the medical records of a patient diagnosed with breast angiosarcoma who underwent radical mastectomy and was found to have multiple lung metastases 3 years after surgery and renal pelvic metastasis 4 years after surgery. The patient underwent robot-assisted laparoscopic radical nephroureterectomy and sleeve resection of the intramural segment of the ureter, and postoperative pathology and immunohistochemical staining confirmed the diagnosis of renal pelvic metastasis of breast angiosarcoma. The patient received anlotinib for lung metastases following surgery and was followed up for 4 months after surgery.Currently, the patient has symptoms of coughing and hemoptysis but no other discomfort. The diagnosis and treatment of this rare malignant tumor remain challenging.